KESUKSESAN ONLINE LEARNING: PENILAIAN DENGAN KONSTRUK KESUKSESAN DELONE DAN MCLEAN PADA MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS DI BALI SELAMA MASA PANDEMI COVID-19 - Gusi Putu Lestara Permana; Ayu Fiqih Wulandari; I Gusti Ngurah Darma Paramartha (Jurnal Ilmu Akuntansi, 2021)
The objective of this study is to determine the success of online learning: an assessment with the success construct of Delone and Mclean on students majoring in accounting at universities in Bali. The population in this study were students of the Accounting study program at the University of Bali. Sample selection method will be determined by using purposive sampling technique. Data collection techniques by means of questionnaires distributed with google form, then data analysis with Partial Least Square (PLS) approach. This study provides the results that the DeLone and McLean model can be used in assessing the success of online learning for students majoring in accounting at universities in Bali. According to researchers, the implementation of teaching and learning activities carried out online in the midst of the Covid-19 outbreak has been successfully implemented. online learning is able to overcome the limitations of space and time due to regulations not to carry out teaching and learning activities that are carried out directly.